2015
DOI: 10.1016/j.jiph.2015.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii clonal lineages I and II harboring different carbapenem-hydrolyzing-β-lactamase genes are widespread among hospitalized burn patients in Tehran

Abstract: The aim of this study was to analyze antimicrobial resistance patterns and their encoding genes and genotypic diversity of Acinetobacter baumannii isolated from burn patients in Tehran, Iran. The presence of extended-spectrum beta-lactamase- and blaOXA-encoding genes among 37 multidrug resistant (MDR) A. baumannii strains isolated from patients hospitalized in a teaching hospital in Tehran was evaluated. Susceptibility to 7 antibiotics was tested by disk agar diffusion and to polymyxin B and colistin was teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…We confirmed the implication of carbapenem-resistant ACB complex isolates in the vast majority of clinical infections and nosocomial outbreaks that involved Acinetobacter isolates, as observed previously in Germany over a 5-year period [ 11 ]. Our findings were also in agreement with the known higher risk of infection by A. baumannii in burn patients in hospital settings, as already reported in Switzerland [ 12 ] and in other countries [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…We confirmed the implication of carbapenem-resistant ACB complex isolates in the vast majority of clinical infections and nosocomial outbreaks that involved Acinetobacter isolates, as observed previously in Germany over a 5-year period [ 11 ]. Our findings were also in agreement with the known higher risk of infection by A. baumannii in burn patients in hospital settings, as already reported in Switzerland [ 12 ] and in other countries [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, 41.7% of gram-negative bacteria, including A. baumannii, were MDR strains and 60% were positive simultaneously for metalo beta lactamase and AmpC production. Mahdian from Tehran and Khadidja from Aljazira reported that 70.3% and 93.6% of isolated A. baumannii from clinical specimens were found to be MDR strains (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Its infections have become critical challenge to health care systems due to increasing levels of resistance to antimicrobial agents in nosocomial isolates of A. baumannii ( Cai et al, 2012 ; Moradi et al, 2015 ). In developing countries, including Iran, the occurrence of carbapenem non-susceptinle A. baumannii (CNSAb) infections is a growing problem in hospitalized burn patients ( Mahdian et al, 2015 ; Zowawi et al, 2015 ). Inadequate management of the antibiotic therapy of CNSAb infections often leads to the emergence of extensive and pandrug resistant (XDR and PDR) CNSAb strains, which present significant health challenges by prolonging hospitalization, treatment failures, and increased mortality ( Liu et al, 2014b ).…”
Section: Introductionmentioning
confidence: 99%